Pilot plant study of recovery of lactic acid from ethyl lactate - Barve, Prashant P.; Rahman, Imran; Kulkarni, Bhaskar D. (Organic Process Research & Development, 2009)
Purified lactic acid is used for production of biodegradable polymer. Esterification with ethanol and subsequent hydrolysis in distillation columns to produce purified lactic acid without catalyst has obvious advantages. In this paper, we present a pilot-plant study of ethyl lactate hydrolysis to produce 3.86 kg/h lactic acid (99.85% purity) using three distillation columns. Simulation of distillation columns at steady state has been carried out, and the results obtained tally with the experimental results of the pilot plant.

Adsorption of fluoride from aqueous solution by alumina of alkoxide nature: batch and continuous operation - Kamble, Sanjay P.; Deshpande, Gunavant; Barve, Prashant P.; Rayalu, Sadhana; Labhsetwar, Nitin K.; Malyshew, Alexander; Kulkarni, Bhaskar D. (Desalination, 2010)
In this investigation, we report the adsorption potential of alkoxide origin alumina for defluoridation of drinking water using batch and continuous mode of operations. The effects of different operating parameters such as adsorbent dose, initial fluoride concentration, pH of the solution and interfering ions (usually present in groundwater) were studied with a view to understand the adsorption behavior of the material under various conditions. A thermodynamic study shows that the adsorption of fluoride by alkoxide origin alumina is an exothermic and spontaneous process. The kinetic results showed that the fluoride sorption follows pseudo-second-order kinetics. The applicability of adsorbent in the field is also tested through column breakthrough studies. It has been observed that with an increase in the flow rate and initial fluoride concentration, the breakthrough curve becomes sharper and the breakthrough time and adsorbed fluoride ion concentration decrease. The breakthrough curve also becomes steeper as the bed height increases. The alkoxide origin alumina based adsorbent media can be used directly for field applications since it is also commercially available in granular form. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Alkoxide alumina; Breakthrough studies; Fluoride; Kinetic modeling

Kinetic modeling and optimization of operating parameters for transvinylation of lauric acid - Kamble, Sanjay P.; Manjarekar, Onkar; Mawale, Ravi; Kulkarni, Bhaskar D.; Chowdary, Naresh; Gupte, Milind Y.; Barve, Prashant P. (International Journal of Chemical Kinetics, 2012)
The transition metal complex catalyzed transvinylation of carboxylic acid with vinyl acetate monomer is of significant interest to industry. The palladium complex catalyzed transvinylation of lauric acid using vinyl acetate monomer is a reversible reaction. In present article, design of experiments (DOE) statistics is used to study effects of various operating parameters on transvinylation of lauric acid. The kinetic parameters forward and backward rate constants and the thermodynamic parameters such as equilibrium constant and energy of activation of the transvinylation of lauric acid were estimated using the Dynochem model. The optimum operating parameters for the transvinylation of lauric acid were then predicted using the Dynochem model and verified by performing the actual experiments to validate the model. It was found that the experimental results match with the predicted one. (c) 2012 Wiley Periodicals, Inc. Int J Chem Kinet 44: 624634, 2012

Preparation of pure methyl esters from corresponding alkali metal salts of carboxylic acids using carbon dioxide and methanol - Barve, Prashant P.; Kamble, Sanjay P.; Joshi, Jyeshtharaj B.; Gupte, Milind Y.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2012)
In the present article, for the first time, we report the synthesis of alkyl esters by direct esterification of alkali metal salts of carboxylic acids using carbon dioxide and alcohol. Methyl acetate, methyl benzoate, methyl salicylate, and methyl lactate have been synthesized by esterification of sodium acetate, sodium benzoate, sodium salicylate, and calcium lactate, respectively. The esterification reaction was carried out in a batch as well as in a semicontinuous mode of operation. A detailed study on the esterification of calcium lactate using methanol and carbon dioxide was carried out to record the effects of various operating parameters (like CO2 pressure, reaction temperature, moisture content in the calcium lactate, and initial concentrations of calcium lactate) on the esterification reaction. This synthesis route produces highly pure methyl lactate by direct esterification of calcium lactate with calcium carbonate as byproduct. The byproduct calcium carbonate was characterized for its crystallinity, surface area, and pore volume. The process route has the advantage that the synthesized byproduct can be recycled into the fermenter to make corresponding alkali metal lactate or the finely precipitated calcium carbonate can be used for various other applications. Thus, the recovery and recycle of alkali metal is possible providing a pollution free process for synthesis of pure methyl lactate.

Purification of lactic acid via esterification of lactic acid using a packed column, followed by hydrolysis of methyl lactate using three continuously stirred tank reactors (CSTRs) in series: a continuous pilot plant study - Kamble, Sanjay P.; Barve, Prashant P.; Joshi, Jyeshtharaj B.; Rahman, Imran; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2012)
The world market of lactic acid is growing every year, mainly as a solvent and precursor to poly(lactic acid) (PLA). The cost of renewable biomass-derived PLA will have to compete with other synthetic polymers, if it is to grab a significant and sustainable fraction of the market share. It is thus necessary to have efficient and cost-effective technology for the production of pure-grade lactic acid (LA). In this article, a novel cost-effective, eco-friendly continuous process for the production of high-quality lactic acid at pilot plant scale has been demonstrated. The novelty of this process is that, for the first time, we report and use the concept of inverse reactive distillation for the esterification of crude concentrated LA in a continuous countercurrent packed column mode. This allows us to operate the column at higher temperatures, improving the kinetic rate process and leading to shorter columns. This is followed by the hydrolysis of methyl lactate (MLA) in a series of three continuously stirred tank reactors (CSTRs), where LA itself acts as a catalyst. The LA obtained in the pilot plant process shows 99.81% purity (by weight) on water-free basis and has an optical purity of 99.9%. The pilot scale experimental results pertaining to the autocatalytic esterification of LA and hydrolysis of MLA have been compared and validated, with respect to simulated results. The innovations reported here can make the process economically viable for commercial use.

Biodegradable iron chelate for H2S abatement: modeling and optimization using artificial intelligence strategies - Hamid, Aashti; Deshpande, Aniruddha S.; Badhe, Yogesh P.; Barve, Prashant P.; Tambe, Sanjeev S.; Kulkarni, Bhaskar D. (Chemical Engineering Research & Design, 2014)
A batch reactor process for the abatement of a common pollutant, namely, H2S using Fe3+-malic acid chelate (Fe3+-MA) catalyst has been developed. Further, process modeling and optimization was conducted in the three stages with a view to maximize the H2S conversion: (i) sensitivity analysis of process inputs was performed to select the most influential process operating variables and parameters, (ii) an artificial neural network (ANN)-based data-driven process model was developed using the influential process variables and parameters as model inputs, and H2S conversion (%) as the model output, and (iii) the input space of the ANN model was optimized using the artificial immune systems (AIS) formalism. The AIS is a recently proposed stochastic nonlinear search and optimization method based on the human biological immune system and has been introduced in this study for chemical process optimization. The AIS-based optimum process conditions have been compared with those obtained using the genetic algorithms (GA) formalism. The AIS-optimized process conditions leading to high (approximate to 97%) H2S conversion, were tested experimentally and the results obtained thereby show an excellent match with the AIS-maximized H2S conversion. It was also observed that the AIS required lesser number of generations and function evaluations to reach the convergence when compared with the GA. (C) 2013 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Artificial immune systems; Artificial neural networks; Batch reactor; Genetic algorithms; Sensitivity analysis